Developing English Textbook for Elementary school of the Sixth Grade Students - Melia Indah Sari; Agus Triyogo; Ayu Oktaviani (Institut Agama Islam Negeri Palopo, 2021)
The objectives of the study was to develop the textbook for Elementary school of the sixth grade students. The population were eighteen students at the sixth grade A class. Nowadays character building was a national movement in Indonesia. The educators asked to integrate it in the learning process, but unfortunately, there are still many teachers that still had difficult in integrating character building in classroom. In English class character building can be integrated through inserting culture in the material, therefore the students are not only learning about the material but they also learned about the value of the culture. The purpose of this research was develop English material for sixth grade students based on character building. The method of this study was Research and Development (R&D) by ADDIE model (1990) was applied Analysis, Design, Development, Implementation and evaluation the product. The subjects of research were the students at elementary school of sixth grade. The result of research showed that the textbook developed was appropriate to the students’ needs and curriculum. The writer concluded that developing English textbook for Elementary school at sixth grade students of SD IT An-nida Lubuklinggau got positive response from six grade students because it can help easier for students comprehend the material clearly. So in this study, the textbook can help students facilitate learning English in the classroom.